MINDSET OF THE FUTURE OF STREET TRADER IN TERAS MALIOBORO - Oktarina Abizia; Sugiyanto Sugiyanto; Rini Dorojati; Irsasri Irsasri (Bajang Institute, 2023)
Malioboro as the icon of the city of Yogyakarta and the philosophical axis is included in the world heritage nomination which connects the imaginary line of the South Coast, Yogyakarta Mataram Palace, Tugu Palputih and Mount Merapi. The presence of Malioboro since 1817 has attracted street vendors (PKL). In 2022 the number of Malioboro PKL will be 1838 traders, and all of them selling in the halls of Jalan Malioboro. These street vendors are an attraction for tourists because of the unique tradition of selling. Research with a qualitative approach, information is determined, primary and secondary data collected through observation, interviews and documentation studies. Secondary data from electronic media and print media as well as local government. Primary and secondary data are integrated into analysis content. Data validation through credibility, transferability and conformability tests. The research results show that starting January 26 2022 the relocation of Malioboro street vendors to Teras Malioboro 1 and Teras Malioboro 2 (one year of street vendor relocation) did not improve the welfare of street vendors but instead brought sorrow, because out of 1838 street vendors 70% of street vendors had decreased income. On the other hand, the relocation of Malioboro street vendors is a design for economic management as well as strengthening the carrying capacity of the Malioboro area as a pedestrian-oriented non-motorised space, so that the concept of transportation used is local becak and horse carts, with the aim of increasing the class of tourists visiting Jogja and tourists can see the combination of local wisdom and modern management means that street vendors and local governments have different mindsets.